Get smart's Bruce and Lloyd. Out of control - Gartner, Alex.; Lazar, Andrew; Ewing, Michael; Green, William; Astle, Tom J.; Ember, Matt.; Junger, Gil.; Oka, Masi.; Torrence, Nate.; Mays, Jayma; Miller, Larry, 1953-; Warburton, Patrick; et al. (Burbank, CA : Warner Home Video, 2008)
Bruce and Lloyd stumble into an adventure when the R&D smarties are out of the lab and way out of their comfort zones as they scramble to find their new invention, an invisibility cloak, that has somehow gotten lost and they need to find it before KAOS does. Learning on the fly how to be a spy is a big-time challenge, especially since the whole invisibility thing really complicates matters.
Title from container.
Special features: Bruce & Lloyd tech: the "real science" behind the movie's gadgets; "Confessions of a lab tech" featurette; "Cue the anti-follicular device" featurette.
Director of photography, Luke Geissbuhler ; editors, Dean Holland, Mike Sale, Adam Wolfe ; music, Paul Linford ; production designer, Stefania Cella.
Masi Oka, Nate Torrence, Jayma Mays, Larry Miller, Patrick Warburton.
MPAA rating: PG-13; crude humor and some language.
DVD, region 1, full screen (1.33:1) and widescreen (matted, enhanced) presentation; Dolby Digital 5.1 surround, dual- layer, NTSC.
Keywords: Laboratory technicians -- Drama; Inventions -- Drama; Spies -- Drama; Comedy films; Adventure films; Video recordings for the hearing impaired; Fiction films; Feature films; Comedy -- Feature; Adventure -- Feature; Comedy films; Adventure films; Feature films